Spontaneous Bilateral Putamen Hemorrhagic Stroke : A Case Report - Suisan, Yohan Christian; Ismayani, Kanti; Adam, Kamila; Hartanto, Edwin; Yujin, Jung (Nommensen Journal of Medicine, 2023)
Background: Intracerebral hemorrhage is associated with a high mortality and disability rate, 40% of which happened in non-traumatic ICH patients. Putamen hemorrhage is the most common cause of ICH and strongly associated with hypertension. Until now, bilateral putamen hemorrhagic stroke is still a rare case. Case: Male, 54 years old, admitted to the ER for being unconscious 1 hour earlier. The patient had a history of hypertension but did not receive any treatment. The patient also had a history of schizophrenia and was taking Clozapine, Trifluoperazine, Sertraline, and Dimenhydrinate. Patient was presented with GCS 112, blood pressure 176/104 mmHg, SpO2 98%. Other physical examinations were within normal limits. Head CT scan showed acute ICH in the right putamen (vol ±7.8cc) and left putamen (vol ±20.7cc). Conservative management was given, but there was no neurological improvement. On day 14, complications of pneumonia occurred and the patient later died due to cardiopulmonary arrest. Discussion: Spontaneous bilateral putamen hemorrhagic stroke is a rare type of ICH and loss of consciousness is the main manifestation of the condition. Hypertension is the most common etiology of bleeding, but the exact mechanism is still unknown. Mortality in patients with spontaneous bilateral putamen bleeding is very high and to date, conservative therapy is the main treatment for patients with these conditions. Conclusion: Spontaneous bilateral putamen hemorrhagic stroke is a rare case with a high mortality rate and so far, the main treatment for this case is conservative management. Keywords: stroke, ICH, bilateral, putamen